Caracterización de la diversidad genotípica de los hemoparásitos bovinos Babesia bovis, Babesia bigemina y Anaplasma marginale - Guillemi, Eliana Carolina (2013)
Ticks are the main vectors involved in pathogen transmission to domestic and wild animals worldwide. In Argentina, the tick species Rhipicephalus microplus is the vector for\ntwo important livestock diseases, the Babesiosis and the Anaplasmosis. The pathogens responsible for these diseases are the protozoan Babesia bovis and Babesia bigemina and the bacteria Anaplasma marginale; all of them are obligate intracellular agents of the bovine erythrocyte. The study of population diversity of these pathogens at a genetic level\nrepresents a fundamental approach aimed to elucidate the impact of factors such as transmissibility and the underlying population structure. In this work, we have developed a tool for the epidemiological study at the molecular level based on sequencing of multiple loci (MLST) for each of the three pathogens. The\nimplementation of this tool allowed genotypic characterization and discrimination of\ndifferent isolates. The implementation of phylogenetic studies and statistical programs\nallowed studying aspects related to previous evolutionary processes.\nAs a result of the analysis of field isolates, we obtained findings suggestive of a wide diverse population and presence of co-infections with different genotypic variants in a\nsingle bovine host. We experimentally reproduced co-infection with two distinct genotypes of B. bovis and A. marginale in order to understand the dynamics of the interaction between\nthe two strains in the same animal as a highly likely event in enzootic areas and where high levels of ticks are found. This thesis contributes to the study of the diversity and population structure of hemoparasites B. bovis, B. bigemina and A. marginale through the development of a\nmolecular typing tool.\n